Análise em bacias hidrográficas: contribuição metodológica para o diagnóstico ambiental - Carvalho, Ana Gabriela Bueno Melo de [UNESP] (2013)
The small watersheds directly influence the quality of life of the cities, and the methodologies for environmental assessment in watersheds, mostly extend to large watersheds, comprising several municipalities, which hinders participatory management and effective. In general, proposed management alternatives for small watersheds guarantee the applicability of the methodology, as managements plans requiring the accession of several municipalities are not always applicable to lack of interest and participation of all municipalities involved. There is a need further studies and propose methodologies applicable to the definition of the intensity of environmental degradation in watersheds small, reaching a single municipality in order to subsidize the government to make decisions regarding the management, the recovery and the creation of areas of urban expansion, making the impacts of land use as small as possible. In this context, the objective of this research is to propose a cartographic model of environmental assessment of the physical environment for small watersheds of different land uses based on the concept of ecodynamics Tricart (1977). It was adopted as the study area Ilha Solteira - SP, which in 1968 had its urban layout planned and built to house workers in the construction of the hydroelectric plant of Ilha Solteira. The council was created on December 30, 1991. In this study, we will apply two different methodologies for assessing environmental quality, the environmental fragility of Crepani et al (1996) and diagnostic physical conservationist watershed adapted Beltrame (1994). As a result, the research developed a cartographic model entitled Diagnosis of the Physical, which in comparison with the other models tested, had defined borders between classes making the map cleaner and simplified. It is noteworthy that all these map products will provide subsidies for public decision-making in order to minimize future...